A Preliminary Study on the Need for Psychological Interventions for Injury Rehabilitation in Youth Footballer - Satwika, Putu; Safitri, Rizka (JSKK (Jurnal Sains Keolahragaan dan Kesehatan), 2025)
Psychological responses can also be found in injured soccer players. There is limited literature on the availability of psychological interventions that can help athletes return to training and competition after injury in the Indonesian context. This study aims to analyze the need for psychological interventions to support post- injury medical rehabilitation in adolescent soccer athletes. Rapid Qualitative Assessment A survey was conducted with a youth soccer player, a coach, and a physiotherapist to understand the cognitive, emotional, and behavioral responses of youth soccer players undergoing injury rehabilitation. Data analysis was conducted using thematic analysis to generate themes regarding player reactions to injury, support received, and expectations regarding needed psychological interventions. Based on the resulting themes, intervention needs were identified related to managing negative emotions and interpretations due to injury, fostering motivation for recovery and encouraging behaviors that support rehabilitation, and social support. These needs can serve as a reference in determining psychological intervention methods for assisting youth soccer players who experience injuries.. Keywords: analysis needs, interventions psychology, rehabilitation injury, youth soccer